PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP PERTUMBUHAN BEBERAPA BENIH ASAL KLON KAKAO (Theobroma cacao l.) DI PEMBIBITAN - Hasmawi Hasyim; Hadriman Khair; Ridho Ardinata (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractThis study to determine the growth response of several types of clones of cocoa (Theobroma cacao L.) with an organic fertilizer in polybag. The design used was Randomized Design Group factorial with two factors were studied, namely: organic fertilizer factor which is denoted by the letter